Development of duststorm attenuation model for microwave links - Islam, Md. Rafiqul; Khalifa, Othman Omran; Al-Khateeb, Khalid A. Saeed; Elabdin, Zain; Elsheikh, Elfatih A. A. (2010)
Duststorms are significant meteorological phenomenon occur for a significant percentage of time in arid and semi arid areas especially at African Sahara and Middle East. Measurements at existing microwave links show that the duststorms can potentially result in serious attenuation in signal level especially at Ku band and higher frequencies with direct impact on telecommunications system performance. Very limited research has been done to predict the attenuation even the scarcity of measured data forces the researcher to work for the duststorm prediction modeling.